2004
DOI: 10.3310/hta8380
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and cost-effectiveness of clopidogrel and modified-release dipyridamole in the secondary prevention of occlusive vascular events: a systematic review and economic evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 237 publications
0
40
0
Order By: Relevance
“…These estimates are based on previous work 201 which employed systematic approaches to identify appropriate utility estimates to apply to patients with ischaemic heart disease, myocardial infarction and stroke, representing the major health states of the model.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…These estimates are based on previous work 201 which employed systematic approaches to identify appropriate utility estimates to apply to patients with ischaemic heart disease, myocardial infarction and stroke, representing the major health states of the model.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…However, in light of the current evidence, some of the more recently issued recommendations suggest that MR-dipyridamole combined with aspirin may be preferable to aspirin monotherapy and possibly to clopidogrel monotherapy (e.g., ACCP 2004 [26]; National Institute for Health and Clinical Excellence 2005 [26]). One of the points in favor of the combination is its positive cost-benefit ratio for stroke prevention (at least for the first 2 years after stroke) [27].…”
Section: Treatment Guidelines and Evidence-based Prescribingmentioning
confidence: 99%
“…inclusion/exclusion of non-vascular death as a health state. They found that model predictions were strongly sensitive to this structural assumption, with potential impact on funding decisions [17]. In another model commissioned by the NICE comparing alternative management strategies for lung cancer, the cost-effectiveness results were most sensitive to the choice of survival functions (Weibull vs. log-logistic) used to estimate overall survival [18].…”
Section: Scenario Analysismentioning
confidence: 98%